The third genotypic clusters of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) found in Bangladesh - Jahan, SMH; Lee, KY; Howlader, MIA (Bangladesh Journal of Agricultural Research, 2015)
The sweetpotato whitefly, Bemisia tabaci is a species complex that possessed several biotypes including different genotypic clusters within species, which may differ from each other genetically and physiologically but morphologically alike. This study was performed by molecular analysis for easy identification of whitefly and describes its biotype throughout Bangladesh. Whiteflies have been identified from different places of Bangladesh based on mitochondrial cytochrome oxidase subunit I (mtCOI) gene and 16S ribosomal RNA gene sequences analysis. The mtCOI sequences of BW3 (collected from eastern part of Bangladesh) whitefly were diverged by 14.5% and 15.1% compared with B and Q biotypes from Korea and it also diverged by 15.4% and 13.7% from each other compared to BW1 (collected from southern part of Bangladesh) and BW2 (collected from northern part of Bangladesh), respectively within the country. The 16S rRNA sequences of BW3 whitefly were more deviated by 41.5%, 10.7%, 42.7% and 12.6% compared with the country populations from BW1, BW2, B and Q biotypes, respectively. Moreover, it showed high divergences from indigenous whiteflies of southern and northern part of Bangladesh which clustered in a different clade on both mtCOI and 16S rRNA phylogeny. Therefore, till date three genotypic cluster of indigenous whitefly BW1, BW2 and BW3 are identified from Bangladesh. Bangladesh J. Agril. Res. 40(1): 1-16, March 2015